Osborn Award 1958 (International Library of African Music, 1958)
Through the continued generosity of the Dr. Tom Osborn Memorial Foundation, the Society has again this year been enabled to make Osborn Awards for the best recordings of the year. The standard of performance of the recordings put forward from which the Committee made their choice was not quite as high as in previous years. Some of the tribes from which recordings were taken are not considered to be in the top flight of Africa’s folk musicians. However, the awards were well merited and the selected items will be appearing shortly on a 12 inch long playing record for public release.
Keywords: African Music